Pembuatan Aplikasi Penataan Rekam Medis Berbasis Web Application di Fisioterapi Rumah Sakit Umum Citra Bunda Medical Center Kota Padang - Ariesa, Dhini; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
In this paper discussed the Medical Records Application Development Planning Web-Based Application in Physiotherapy General Hospital Citra Bunda Medical Centrel Padang. This study aims to describe the application process managing medical records using the programming language PHP (Hypertext Preprocessor) web-based application, this application is used as a tool to facilitate therapists in finding medical records of patients in the room physiotherapy General Hospital Citra Bunda Medical Centrel Kota Padang .This method of research used in this paper is descriptive method with qualitative approach. This method is an effective measure used in the manufacture of paper, that is by describing how making the application and explain in narrative form. Data were collected through observation and interviews directly to the General Hospital physiotherapy room Citra Bunda Medical Centrel Kota Padang. Based on the arrangement of medical records application creation using PHP (Hypertext Preprocessor) is a web-based application, the manufacturing process can be summarized as follows: 1) creating a database using XAMP, on XAMP created tables or databases; 2) designing and designing the look of the application, in this case the application is designed according to the needs of therapists; 3) coding, ie the process of entering the programming language to run the program; 4) unites phpmyadmindengandatabase that has been created and linked to php using ODBC (Open Database Connectivity).Keyword: Medical record , Web Aplication.